Minimally Invasive Surgery: A Conceptual Review - Rully Hanafi Dahlan; Sevline Estethia Ompusunggu; Farid Yudoyono (Neurologico Spinale Medico Chirurgico, 2019)
We are living in an era that performs minimally invasive approaches to many surgical aspects, and spine surgery is not an exception. Nowadays, minimally invasive spine surgery is a routine procedure in many countries around the world. It began in the mid-twentieth century and has now developed into a large feld of progressive spinalsurgery. This paper will review the philosophy, indications, patient selections, advantages, and disadvantages of minimally invasive spinal surgery